Possession - Byatt, A. S. 1936- (Antonia Susan) (Philippines Manufactured and distributed by Warner Home Video, 2002)
Roland, an academic researcher, finds letters from a famous married Victorian poet addressed to another woman, a less well-known poet, Christabel LaMotte. He contacts Maud, an expert on LaMotte's life and work. Despite her skepticism, the two begin to investigate, and uncover a wealth of information about the affair between the two poets.
Disc 1: 56 min. - disc 2: 47 min.
Originally produced as a motion picture in 2002.
Based on the novel by A.S. Byatt.
VCD.
Directed by Neil LaBute ; screenplay by Henry David Hwang and Laura Jones and Neil Labute ; produced by Paul Weinstein, Barry Levinson ; co-producer Stephen Pevner.
Gwyneth Paltrow, Aaron Eckhart, Jeremy Northam, Jennifer Ehle.
Keywords: Love poetry, Romance -- Drama; Poetry -- History and criticism -- Drama; Poets -- Drama; Manuscripts -- Collectors and collecting -- England -- Drama; Poets, English -- Drama; Love stories; Historical films